2012
DOI: 10.1093/eurjhf/hfs123
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term benefits of immunoadsorption in β1‐adrenoceptor autoantibody‐positive transplant candidates with dilated cardiomyopathy

Abstract: AimsProlongation of waiting times for heart transplantation (HTx) increases the need for new therapies. In short-term follow-up studies, immunoadsorption (IA) appeared beneficial in dilated cardiomyopathy (DCM) associated with b 1 -adrenoreceptor-autoantibodies (b 1 -AABs). This study aimed to investigate the long-term benefits of IA in HTx candidates with DCM, patients' responsiveness to IA, and the impact of b 1 -AAB removal on IA results. Methods and resultsIn a single-centre retrospective study of prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 34 publications
5
70
1
2
Order By: Relevance
“…Short-and long-term results of unspecific IA were also better in b 1 -AAB positive than b 1 -AAB negative patients [13,20]. Today IA is accepted as a therapy option for idiopathic DCM [21].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Short-and long-term results of unspecific IA were also better in b 1 -AAB positive than b 1 -AAB negative patients [13,20]. Today IA is accepted as a therapy option for idiopathic DCM [21].…”
Section: Introductionmentioning
confidence: 87%
“…Thereafter, a large number of studies evaluating the short-term ( 1 year) efficacy of IA in idiopathic DCM showed significant improvement in LV ejection fraction (LVEF) and/or cardiac index for both unselective IgG removal and selective b 1 -AAB removal [9,15e19]. A large recently published long-term follow-up study also showed that b 1 -AAB removal by both specific and unspecific immunoadsorption (IA) can improve heart function in more than 70% of patients with end-stage idiopathic DCM, allowing long-term cardiac stability with a 5-year survival probability of more than 69% without the necessity of HTx or mechanical circulatory support [13].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have also shown long-term effects of IA with respect to the improvement of cardiac function, morphology, and the symptom state (Dandel et al 2012;Müller et al 2000). In addition, one of these studies could demonstrate that IA may also be associated with reduced rates of heart transplantation and the need for (artificial) ventricular assist devices during a follow-up time of up to 14.7 years (Dandel et al 2012). However, all these studies were either uncontrolled or open controlled studies which compared the effects of IA to conventional therapy but without any sham intervention in the control group.…”
Section: Immunoadsorption As a Therapeutic Option In Dcmmentioning
confidence: 98%
“…Thus, currently available data have demonstrated that IA/IgG resulted in significant increase in cardiac functional and morphological parameters, symptoms' relief, heart failure related clinical biomarkers (Dörffel et al 1997;Felix et al 2000;Müller et al 2000;Felix et al 2002;Staudt et al 2002Staudt et al , 2005Staudt et al , 2006Staudt et al , 2010Doesch et al 2010;Pokrovsky et al 2013), increased exercise tolerance , and improvement of endothelial function (Bulut et al 2011). Two studies have also shown long-term effects of IA with respect to the improvement of cardiac function, morphology, and the symptom state (Dandel et al 2012;Müller et al 2000). In addition, one of these studies could demonstrate that IA may also be associated with reduced rates of heart transplantation and the need for (artificial) ventricular assist devices during a follow-up time of up to 14.7 years (Dandel et al 2012).…”
Section: Immunoadsorption As a Therapeutic Option In Dcmmentioning
confidence: 99%
“…In this context, the elimination of pathogenetic AABs, such as the pathogenic β 1-AABs, via apheresis techniques has been suggested for Chagas heart disease [90] . The idea of using apheresis in the treatment of Chagas heart disease is supported by the well-documented benefits of β -1-AAB immunoadsorption in patients with DCM [91] .…”
Section: Therapymentioning
confidence: 99%